PENGARUH KONSENTRASI LARUTAN DAUN JAMBU BIJI (Psidium guajava) DAN LAMA PERENDAMAN TERHADAP KUALITAS TELUR AYAM RAS - Ernawati, Tri; Karisoh, Linda Ch. M.; Hadju, Rahmawaty; Siswosubroto, Surtijono E. (ZOOTEC, 2019)
THE EFFECT OF GUAVA LEAF SOLUTION CONCENTRATION AND SOAKING DURATION ON THE QUALITY OF CHICKEN EGGS.      This study aims to determine the effect of guava leaf solution concentration and soaking time on the quality of chicken eggs. This research was conducted from November to December 2018, at the Laboratory of Animal Product Technology, Faculty of Animal Husbandry, Sam Ratulangi University, Manado. The method used is Completely Randomized Design (CRD) with a factorial pattern consisting of 2 factors. Factor A was the concentration of solution of guava leaves and factor B is the length of immersion with 4 replications. The treatments used are: Factor A concentration of solution of guava leaves A1 = 3%, A2 = 6%, A3 = 9%, A4 = 12%. Factor B was duration of immersion B1 = 6 hours, B2 = 12 hours, B3 = 18 hours, B4 = 24 hours. The variables analyzed were a decrease in egg weight, egg white index and egg yolk index. Data obtained were analyzed by variety. If there are significant differences between treatments, it will be continued with Duncan Test. The results of the variance analysis showed that the interaction had a significant effect (P <0.05) on the decrease in egg weight and did not significantly influence (P> 0.05) on the egg white index and egg yolk index. Duncan's Test results for decreasing egg weight showed the concentration of guava leaf solution 3% and soaking time 6 hours  gave good results for the quality of chicken eggs. It was concluded that the concentration of 3% and the soaking time of 6 hours gives good results on decreasing egg weight. As for the egg white index and egg yolk index showed good results with concentration of 12% and 24-hour immersion time. Keywords: Guava leaf, Egg weight, Egg white index, Egg yolk index.